Social Comparison and Perceived Breach of Psychological Contract: Their Effects on Burnout in a Multigroup Analysis - Topa Cantisano, Gabriela; Morales Domínguez, J. Francisco; Caeiro García, J. Luis (The Spanish Journal of Psychology, 2007)
This study focuses on the mediator role of social comparison in the relationship between perceived breach of psychological contract and burnout. A previous model showing the hypothesized effects of perceived breach on burnout, both direct and mediated, is proposed. The final model reached an optimal fit to the data and was confirmed through multigroup analysis using a sample of Spanish teachers (N = 401) belonging to preprimary, primary, and secondary schools. Multigroup analyses showed that the model fit all groups adequately